REGENERATION OF THE DESIGN OF WEAVING AND EMBROIDERY PATTERNS BASED ON ARTIFICIAL INTELLIGENCE TECHNOLOGIES - MA , WENJUAN; CHUBOTINA , I. M. (Art and Design, 2024)
Purpose of this work is to determine the feasibility of using AIGC (Artificial Intelligence Generated Content) technology to restore the design of traditional Yao patterns in order to protect and preserve the culture of the Yao ethnic group, and at the same time contribute to the modernization of the application of traditional arts. Methodology: In this study, based on the classification and combing through Yao weaving and embroidery patterns through literature research, the two selected design patterns are coded and extracted, and AIGC (Artificial Intelligence Generated Automatic Generation Contents) technology is cited to carry out regeneration design of the patterns. Results: By studying the process of creation and evolution of Yao patterns, it was found that its unique cultural and aesthetic value warrants study and preservation. It was found that patterns created using AIGC technology not only retain the basic elements of traditional patterns, but also introduce various design innovations. These newly created templates have a high visual aesthetic and can be applied to the design of Yao derivative cultures. Scientific novelty of the study consists in the identification of the main characteristics of the traditional patterns of the Yao people, and the proposed approach to their preservation and integration into modern design. By overcoming the limitations of traditional design, this study combines AIGC technology with national traditional culture. Practical significance: This study is of great scientific significance because it not only provides a new method for digital preservation and innovative design of Yao patterns, but also contributes to the study of the application of artificial intelligence in pattern innovation. Research materials can be used both in educational courses and in project design practices.